Simultaneous DualEELS and EDS analysis across the ohmic contact region in 3D NAND storage and FinFET electronic devices. (July 2017) - Longo, P.; Zhang, H.; Twesten, R.D.
Abstract: The complementary nature of electron energy-loss spectroscopy (EELS) and energy dispersive spectroscopy (EDS) signals makes it highly desirable to acquire both during transmission electron microscope (TEM) investigations of materials. With ongoing improvements in electron instrumentation and detectors, it is now practical to acquire joint EELS-EDS spectrum image data for materials analysis, all the way from large area mapping down to atomic scale analysis. This paper shows data over a range of different experimental conditions that show the complementary nature of the techniques and highlight the strength of each. In particular, the attention is focused on the chemical and compositional analysis of samples obtained from the latest generation of 3D NAND memory and also FINFET semiconductor devices currently available in the market.